The Role of Islamic Religious Education (PAI) in Preventing Free Association at SMPN 1 Jogorogo - Chervin Arrohman Laksana; Muh. Nur Rochim Maksum (al-Afkar, Journal For Islamic Studies, 2024)
This study uses qualitative research methodology with phenomenological approach to understand juvenile delinquency in SMPN 1 Jogorogo. The purpose of this study was to analyze the effectiveness of faith-based approaches, especially Islamic Religious Education (PAI), in preventing free sex behavior in the school environment. The research method involves collecting primary data through interviews with principals, religious teachers, and students, observation of student behavior, and related documentation. Secondary data were obtained from public sources related to the organizational structure and role of PAI at SMPN 1 Jogorogo. The validity of the data is obtained through careful observation and using triangulation, both from the source and the method. Data analysis using the Miles and Huberman model, involves the stages of data reduction, data presentation, and conclusions. The conclusion of this study shows that religious approaches, through study and tahfidz activities, are effective in reducing cases of juvenile delinquency. Challenges faced, such as student disobedience and lack of parental involvement, can be addressed by strengthening communication between schools and families.